‘In both our languages’: Greek-Latin code-switching in Roman literature - Mullen, Alex (Sage, 2015)
After a short introduction to code-switching and Classics, this article offers an overview of the phenomenon of code-switching in Roman literature with some comments on possible generic restrictions, followed by a survey of Roman attitudes to the practice. The analysis then focuses on Roman letter writing and investigates code-switching in the second-century correspondence of Fronto (mainly letters between Marcus Aurelius, who became Emperor in AD 161, and his tutor Fronto). This discussion uses part of a new detailed database of Greek code-switches in Roman epistolography and is largely sociolinguistic in approach. It makes comparisons with other ancient and modern corpora where possible and highlights the value of code-switching research in responding to a range of (socio)linguistic, literary and historical questions.